Structural model and characteristics of kindergarten teachers’ occupational beliefs in China: A grounded theory approach - Zhang, Lei; Guo, Qiang; Zhu, Jie; Wang, Tingzhao; Hu, Bisheng (Frontiers in Psychology, 2022)
To explore the characteristics of kindergarten teachers’ occupational beliefs in China, 24 public and private kindergarten teachers were interviewed, their teaching was observed, and teaching reflection notes and educational essays were collected. A structural model was subsequently developed. Based on grounded theory, the information was coded at three levels and tested for theoretical saturation. The results demonstrated that the occupational beliefs of kindergarten teachers consisted of occupational cognition, occupational endurance, occupational expectation, and occupational intention, and these four core elements were not independent. Although there were characteristics common to public and private kindergarten teachers’ occupational beliefs, they also had distinct characteristics. The occupational beliefs of public kindergarten teachers were relatively stable, yet those of private kindergarten teachers were not. Moreover, most public kindergarten teachers were willing to stay in their teaching jobs. These findings reveal the composition and characteristics of Chinese kindergarten teachers’ occupational beliefs and the relationship between kindergarten teachers’ turnover and occupational beliefs.